الألعاب الالكترونية ومدى تأثيرها في تكوين تفكير الطفل - طالبي محمد مروان; د/ساحي علي (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة إن تأثير الألعاب الإلكترونية على تفكير الطفل. تُعدّ انشغغغغغغغال الأافال واحدل ما ا لدوا ع الرئيسغغية للهل لشغغراء الألعاب الإلكترونية. توضغغض الفرضغغيات ة الدراسغغة أن هاا تأثي را لللعاب الإلكترونية على تفكير الطفل وأن هاا تأثي را إحصائي ا لجاس الطفل ولة الأمر على تفكير الطفل. اسغغتخدما الدراسغغة المالو الوصغغفة واعتمدت على المالو الالري والميدانة لجمع البيانات والمعلومات المتعلقة بموضغغغوع الدراسغغغة. تم إعداد اسغغغتبانة وتو يعلا على أولياء الأمور ة ولايتة ، وتم اختيار عياة ما 60 ولة أمر بطريقة عشوائية بسيطة. توصلا الدراسة إلى أن الأافال يمارسون الألعاب الإلكترونية ة أوقات راغلم، وأن هاا توا ق ا ة ممارسة الألعاب الإلكترونية بيا الأافال. أظلرت الاستجابات المسجلة أي ضا تأثي را إيجابي ا لللعاب الإلكترونية على الأافال، مثل تامية قدراتلم ة التعامل مع التقايات الحديثة. وما الآثار السغغغغلبية، تم اكر احتمالية إصغغغغابة الأافال بلدمان اللعا والانشغغغغغال عا العادات والطاعات. تختتم الدراسغغغغغغة بتقديم مجموعة ما التوصغغغغغغيات المقترحة باا ء على الاتائو والاسغغغغغغتاتاجات الحاصل Summary of the statement: The study examines the impact of electronic games on children's thinking. Children's engagement is one of the main motivations for parents to purchase electronic games. The hypotheses in the study suggest that electronic games have an effect on children's thinking and that there is a statistical effect of the child's gender and parental influence on the child's thinking. The study utilized a descriptive approach and relied on theoretical and field methods to collect data and information related to the study's topic. A questionnaire was prepared and distributed to parents in two states, and a sample of 60 parents was randomly selected. The study found that children engage in electronic games during their leisure time, and there is a consensus among children in practicing electronic games. The recorded responses also indicated a positive impact of electronic games on children, such as enhancing their abilities to deal with modern technologies. Negative effects mentioned include the possibility of children developing addiction to playing and being distracted from habits and responsibilities. The study concludes by providing a set of recommended suggestions based on the results and findings.
دراسة منهجية لجمهور بلدية الاغواط